Los cabildos antioqueños ante la crisis monárquica, 1808-1812 (2009)
ABSTRACT: Based on a close reading of primary sources, this essay analyzes the way in which four cabildos in the Province of Antioquia (northwest Colombia) reacted to the crisis of the Spanish monarchy in 1808. In Antioquia, a group of prominent individuals challenged the authority of Governor Francisco de Ayala, and tried to reassert sovereignty by autonomously naming alcaldes pédaneos y de partido. This marked the beginning of a change of attitude among antioqueños, strengthened by the autonomous movements of Quito and Cartagena, and by the so-called "cry of independence" of Santa Fe. Antioquia's cabildos reassumed sovereignty, formed their own governing junta, wrote their own Constitution, and, in 1813, formed a new state that was declared índependent from Spain.